Assessment of pulmonary function in a follow-up of premature infants: our experience - F. Ciuffini; O. Marijke; A. Lavizzari; B. Ghirardi; S. Musumeci; E. Dusi; M. Colnaghi; F. Mosca (PAGEPress Publications, 2013)
Respiratory diseases are a major cause of morbidity in neonates, especially preterm infants; a long term complication of prematurity such as bronchopulmonary dysplasia (BPD) is particularly relevant today. The exact role of the Pulmonary Function Test (PFT) in this area is not yet well defined; the PFT in newborns and infants - in contrast to what happens in uncooperative children and adults - are routinely used only in a few centers. The assessment of pulmonary function in newborns and infants, however, is nowadays possible with the same reliability that in cooperative patients with the possibility to extend the assessment of polmonary function from bench to bed. The assessment of pulmonary function must be carried out with non invasive and safe methods, at the bedside, with the possibility of continuous monitoring and providing adequate calculation and management of data. The ability to assess lung function helps to define the mechanisms of respiratory failure, improving the treatment and its effects and is therefore a useful tool in the follow-up of newborn and infant with pulmonary disease.